Intra-Articular Osteotomy for Distal Humerus Malunion - René K. Marti; Job Doornberg (Case Reports in Medicine)
Intra-articular osteotomy is considered in the rare case of malunion after a fracture of the distal humerus to restore humeral alignment and gain a functional arc of elbow motion. Traumatic and iatrogenic disruption of the limited blood flow to the distal end of the humerus resulting in avascular necrosis of capitellum or trochlea is a major pitfall of the this technically challenging procedure. Two cases are presented which illustrate the potential problems of intra-articular osteotomy for malunion of the distal humerus.